Divergence of hydraulic traits among tropical forest trees across topographic and vertical environment gradients in Borneo. Issue 6 (26th June 2022) - Bittencourt, Paulo Roberto de Lima; Bartholomew, David C.; Banin, Lindsay F.; Bin Suis, Mohamed Aminur Faiz; Nilus, Reuben; Burslem, David F. R. P.; Rowland, Lucy
Summary: Fine‐scale topographic–edaphic gradients are common in tropical forests and drive species spatial turnover and marked changes in forest structure and function. We evaluate how hydraulic traits of tropical tree species relate to vertical and horizontal spatial niche specialization along such a gradient. Along a topographic–edaphic gradient with uniform climate in Borneo, we measured six key hydraulic traits in 156 individuals of differing heights in 13 species of Dipterocarpaceae. We investigated how hydraulic traits relate to habitat, tree height and their interaction on this gradient. Embolism resistance increased in trees on sandy soils but did not vary with tree height. By contrast, water transport capacity increased on sandier soils and with increasing tree height. Habitat and height only interact for hydraulic efficiency, with slope for height changing from positive to negative from the clay‐rich to the sandier soil. Habitat type influenced trait–trait relationships for all traits except wood density. Our data reveal that variation in the hydraulic traits of dipterocarps is driven by a combination of topographic–edaphic conditions, tree height and taxonomic identity. Our work indicates that hydraulic traits play a significant role in shaping forest structure across topographic–edaphic and vertical gradients and may contribute to niche specialization among dipterocarp species.